Satellite to buoy IoT communications in the Arctic Ocean - Røste, Terje; Yang, Kun; Wen, Chengyuan (Frontiers in Marine Science, 2023)
Internet of things (IoT), to Arctic Ocean areas using Low Earth Orbit (LEO) satellites for communication to and from sensor units on the sea, has become increasingly important. It is challenging to close the link budget from a buoy on sea to a LEO satellite due to restrictions on the availability of power in such installations. Phenomena as scattering from the sea surface and small-scale fading, ionospheric scintillations, diffraction loss at low elevation angles, and power availability in small LEO satellites and models for analysis are described. It is of great importance to have a radio wave propagation model that accurately predicts path loss between an installation on the sea and a LEO satellite taking all loss mechanisms into account. In this paper, a path-loss model for satellite to buoy communications over the sea is described. In this model, maritime propagation phenomena in the radio link include free space loss, scintillation loss caused by the ionosphere, diffraction loss at low elevation angle, and scattering at the sea surface depending on the wave height and small-scale fading. Furthermore, a buoy on the sea surface with strong angular movement will cause a varying receive signal level depending on the antenna diagram. These phenomena are assessed. A link budget for the frequencies 433, 868, and 3,400 MHz is calculated for a LEO satellite at a height of 800 km.